Wishypoofs and hiccups - Citro, Asia (Citro, Asia. Zoey and Sassafras, 2021)
Pip shows up with a new look that's just as surprising to him as it is to Zoey and Sassafras. When they retrace Pip's steps in the forest, they see another magical friend change right before their eyes.